Effect of Mould Size on Compressive Strength of Green Concrete Cubes - Bashir Ahmed Memon; Mahboob Oad; Abdul Hafeez Buller; Sajjad Ahmed Shar; Abdul Salam Buller; Fahad-u-Rehman Abro (Salehan Institute of Higher Education, 2019)
This paper is aimed to evaluate the effect of mould size on compressive strength of concrete cubes made with recyclable concrete aggregates. Natural coarse aggregates were replaced with 50% recycled aggregates from old demolished concrete. Five different mould sizes were used to cast 420 concrete cubes using 1:2:4 mix and 0.55 water/cement ratio. In each size equal number of cubes was cured for 3, 7, 14 and 28-day. After curing, weight of cubes was determined followed by testing for compressive strength in universal load testing machine with gradually increasing load. From the obtained results the strength correction coefficients were computed keeping 28-day cured standard size cubes as control specimens. Also, numerical expression based on regression analysis was developed to predict the compressive strength using weight of cube, area of mould and curing age as input parameter. The numerical equation predicts the compressive strength very well with maximum of 10.86% error with respect to experimental results.